An ethnography of St Helena Bay - A West Coast Town in the age of neoliberalism - Shultz, O (Social Anthropology, 2015)
This dissertation uses ethnography as a means to examine how multiple-scale patterns of interaction between social and ecological systems as they manifest locally in St Helena Bay. The growing integration of the West Coast has brought rapid change in the form of industrial production, urban development and in-migration. The pressure placed on local resources by these processes has been exacerbated by the rationalisation of the local fisheries - there are fewer jobs in the formal industry and small-scale fishing rights have become circumscribed. In the neighbourhood of Laingville, historically-contingent racial categories have become reinvigorated in a context resource scarcity. An autochthonous cultural heritage related to the West Coast has become transposed onto the category of 'real' or 'bona fide' fishers. For those who claim this identity, it serves as a means to legitimate claims to resources while simultaneously excluding the claims of others. A pattern of recurring dichotomies emerges as a defining motif capturing the sense among local people that threatening elements from 'outside' are imposing themselves on the local socio-ecology. For small-scale fishers, the lack of recognition by the state of what they believe is their autochthonous right to access to the marine commons feeds an intense sense of frustration. The act of breaking 'the rules' of the state is perceived by many as an assertion of their rights and thus, of their dignity. In the case of poaching, it is seen by fishers as a means to become an active agent in one's own life, while at the same time making more money than could be made if fishing rules were adhered to. Because of these powerful symbolic and material motivations for breaking the rules, it is something that many people take pride in doing. In contradistinction to this, following the rules of the state is seen as collaborating with the state in undermining one's own socio-economic conditions, and, significantly, in negating one's birthright. For many fishers in Laingville, adhering to the rules is infused stigma